Problems of adapting enterprises in the strategy implementation process. Case of Poland - Noga, Gracjana (Business, Management and Economics Engineering, 2018)
Purpose – The purpose of the article was to analyse the impact of the enterprise adaptation stage on implemented strategy effectiveness. Research methodology – In the theoretical part the method of analysis and critical review of the literature was used. The technique used in the empirical study was paper-and-pencil interviewing (PAPI). In order to investigate relationships, the χ2 Pearson test and the Yule’s Coefficient of Association ϕ were employed. Findings – The article resulting underline the importance of the stage of adapting the enterprise in the strategy implementation process. The organisational structure, skills and knowledge, as well as organisational culture, have a particularly strong impact on the effectiveness of the strategy. Research has not confirmed any relationship between management style and resources. Research limitations – The empirical research was carried out on business organisations from a ranking of 500 innovative businesses of the Institute of Economics of the Polish Academy of Sciences list, what does not ensure that the indicated problems are characteristic for the average companies active in Poland. Practical implications – The obtained results became the basis for defining recommendations, which are practical guidelines for those trying to implement a strategy. It should be noted that the presented practical guidelines are not static research indications and will develop as the organisation and its environment change. Originality/Value – There is a lack of research in Poland, which is focused on the problem of adjusting enterprise in the strategy implementation.